Ranking tourism market performance in EMU countries: results of PROMETHEE – GAIA approach - Durkalic, Danijela; Furtula, Srdjan; Borisavljevic, Katarina (Hotel and Tourism Management, 2019)
Using data from 19 countries of the European Monetary Union (EMU), this paper examines the nature of tourism performance and the ranking of countries according to given parameters in tourism in the period 2012-2017. As tourism cannot be analyzed as an isolated scientific discipline, it is necessary to use a multidimensional and multicriteria approach when studying and researching this field. For this reason, this paper implements a simple methodology for measuring tourism performance in EMU countries using the multicriteria PROMETHEE – GAIA decision model. The paper will, through the analysis of 8 parameters important for the development and evaluation of the tourism industries (number of foreign tourists, number of domestic tourists, quantity of hotel accommodation, cost of living, air pollution, population density, length of railway and number of airports), rank the mentioned countries and provide a deeper analysis of individual parameters. For the entire period of observing and reviewing the performance of the tourism industry, the results of the paper will outline the performance evaluation as well as policy recommendations and conclusions for further consideration and analysis.